2003
DOI: 10.1254/jphs.92.35
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Ca2+-Activated K+ Channel, SK3, in Fibroblast-Like Cells Forming Gap Junctions With Smooth Muscle Cells in the Mouse Small Intestine

Abstract: In the present study, we examined the expression and the localization of apamin-sensitive small conductance Ca(2+)-activated K(+) channels (SK channels) in the mouse intestine. SK3-immunoreactivity (IR) was detected in both ileum and colon. Double staining experiments showed that SK3-IR was colocalized with prolyl 4-hydroxylase (PH(alpha))-IR, but not with c-Kit-IR which are markers of fibroblast cells and the interstitial cells of Cajal (ICC), respectively. Although SK3-IR was colocalized with vimentin-IR, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
83
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(91 citation statements)
references
References 39 publications
(37 reference statements)
8
83
0
Order By: Relevance
“…Our previous study showed PDGFR immunoreactivity in FLC and the co-localization of PDGFR and SK3 immunoreactivities in the murine GI tract (Iino et al, 2009a). Vanderwinden et al (2002) and Fujita et al (2003) showed that SK3 immunoreactivity was preferentially distributed in c-Kit-immunonegative FLC in human and murine GI tracts. From these findings, we postulated that FLC in murine GI musculature possessed SK3 immunoreactivity.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Our previous study showed PDGFR immunoreactivity in FLC and the co-localization of PDGFR and SK3 immunoreactivities in the murine GI tract (Iino et al, 2009a). Vanderwinden et al (2002) and Fujita et al (2003) showed that SK3 immunoreactivity was preferentially distributed in c-Kit-immunonegative FLC in human and murine GI tracts. From these findings, we postulated that FLC in murine GI musculature possessed SK3 immunoreactivity.…”
Section: Discussionmentioning
confidence: 91%
“…CD34 was first reported to be immunohistochemically expressed in the human FLC, but was barely detected in the murine FLC (Vanderwinden et al, 1999(Vanderwinden et al, , 2000(Vanderwinden et al, , 2002. SK3 immunoreactivity has been reported in human and murine FLC (Vanderwinden et al, 2002;Fujita et al, 2003) although some reports showed the expression of SK3 immunoreactivity in ICC of several species (Fujita et al, 2001;Klemm and Lang, 2002;Piotrowska et al, 2003) or in smooth muscle cells of the murine GI tract (Ro et al, 2001). We recently showed that PDGFR immunoreactivity was specifically distributed in FLC in the murine GI musculature and was co-localized with SK3 (Iino et al, 2009a).…”
Section: Introductionmentioning
confidence: 99%
“…Immunohistochemical study was carried out by the method described previously Fujita et al, 2003). Briefly, mice were deeply anesthetized with pentobarbital sodium (50 mg/kg, i.p.…”
Section: Immunohistochemical Study Of C-kit Proteinmentioning
confidence: 99%
“…Moreover, the effect of ATP was significantly reduced in PDGFRα-expressing cells from P2Y 1 -knockout mice, indicating a major role of P2Y 1 in these cells [40] . It is therefore conceivable that these cells are also important mediators of purinergic relaxation in the rat ileum, which harbors SK3-expressing fibroblast-like cells that form gap junctions with smooth muscle cells [42] , as has recently been shown in the murine colon [43] . Another limitation of our study might be that purinergic receptors are also expressed in epithelial cells and hence are involved in secretory processes [44][45][46] .…”
Section: Intracellular Signaling Cascade Following Purinergic Receptomentioning
confidence: 89%